ACE DD genotype is unfavorable to Korean short-term muscle power athletes - Kim, C.-H.; Cho, J.-Y.; Jeon, J. Y.; Koh, Y. G.; Kim, Y. M.; Kim, H. J.; Park, M.; Um, H.-S.; Kim, C. (International Journal of Sports Medicine, 2010)
The purpose of this study was to test the hypothesis that the ACE DD genotype is unfavorably associated with the ultimate power-oriented performance. To test the hypothesis we recruited a total of 848 subjects including 55 international level power-oriented athletes (High-performance), 100 national level power-oriented athletes (Mid-performance) and 693 healthy controls (Control) in Korea. Then the distributions of ACE polymorphism throughout these groups were analyzed. As a result, there was a gradual decrease of frequencies of the DD genotype with advancing levels of performance (Control vs. Mid-performance vs. High-performance=17.2% vs. 10.0% vs. 5.5%, p=0.002). Also, the frequencies of D allele decreased gradually with advancing levels of performance (Control vs. Mid-performance vs. High-performance=42.6% vs. 35.0% vs. 30.9%, p<0.01). Therefore, power-oriented athletes at the top level had a markedly diminished frequency of the DD genotype and the D allele. This finding gave 3.83 times lower probability of success in power-oriented sports for individuals with the DD genotype than those with the II+ID genotype. In conclusion, these results indicate that Korean power-oriented athletes with a lower frequency of the DD genotype had a lower probability of success in power-oriented sports.